Rekonstruksi Akhlak Islam dalam Seni Pertunjukan: Penerapan Pemikiran Al-Zarnuji di Teater Jangkarbumi - Abadi, Muhammad Zidan; Taufikin, Taufikin (Tarbawi : Jurnal Pendidikan Islam, 2024)
Moral education has an important role in shaping good Muslim character, but traditional methods are often less effective in attracting the attention of the younger generation. This research examines the application of Al-Zarnuji's thoughts in the performing arts with a focus on Jangkarbumi Theatre as a case study. Using a descriptive qualitative approach, data was obtained through observation, interviews, and analysis of performance scripts such as Titik or Koma and Demama'an. The results showed that Teater Jangkarbumi's performances successfully integrated Islamic moral values, such as sincerity, patience, and social solidarity, through strong narratives, symbolic gestures, and relevant characters. This performance not only entertains, but also educates the audience, especially the younger generation, by inserting moral messages that are relevant to everyday life. This research confirms the importance of performing arts as an innovative and effective medium of moral education, while offering a dynamic way to integrate Islamic values in modern art. This study enriches the discussion on the adaptation of Islamic teachings in contemporary educational practices, particularly in arts-based character building.